Exploring the Effect of Personality Traits in VR Interaction: The Emergent Role of Perspective-Taking in Task Performance - Katifori, Akrivi; Lougiakis, Christos; Roussou, Maria (Frontiers in Virtual Reality, 2022)
In this work we explore the effect of personality traits on user interaction in virtual reality (VR), on the less widely studied aspect of task performance during object manipulation. We conducted an experiment measuring the performance of 39 users interacting with a virtual environment using the virtual hand metaphor to execute a simple selection and positioning task, with or without virtual obstacles. Our findings suggest concrete correlations between user personality traits and behavior data. Perspective-taking, in particular, seems to be strongly affecting task performance, highlighting the need for further research. Besides the wider implications of our results in relation to the effect of personality on how users experience VR, our main contribution lies in identifying specific traits that should be taken into account when designing experiments involving users performing such tasks. The study of these traits may also significantly advance our understanding of personality traits as part of the user model in a wider range of VR applications, including those offering personalization and recommendation functionality.